Cortical morphometric predictors of autonomic dysfunction in generalized anxiety disorder - Carnevali, Luca; Koenig, Julian (Autonomic neuroscience, 2019)
Generalized anxiety disorder (GAD) is associated with both autonomic dysfunction, notably decreased vagally-mediated heart rate variability (vmHRV), and neurostructural abnormalities. Regional differences in brain morphometry correlate with vmHRV in healthy individuals. Here, we tested the hypothesis that specific focal abnormalities in cortical structure in GAD underpin decreased vmHRV. Adult female patients with GAD (n=17) and matched controls (n=18) underwent structural magnetic resonance imaging after characterization of symptoms and quantification of resting vmHRV derived from continuous pulse oximetry. Cortical reconstruction was performed using the FreeSurfer image analysis suite. A priori analysis was conducted only within brain regions involved in vagal control of heart rate. Compared to controls, patients with GAD showed cortical thinning of the (i) left rostral anterior cingulate cortex, (ii) left medial orbitofrontal cortex, and (iii) right isthmus cingulate gyrus. Significant negative relationships were identified between the severity of anxiety symptoms and cortical thickness of the left medial orbitofrontal cortex and right isthmus cingulate gyrus. Compared to controls, patients with GAD showed decreased vmHRV at rest. In controls only, cortical thickness of the left caudal anterior cingulate cortex correlated positively with resting vmHRV. These results extend evidence in GAD for structural abnormalities within cortical areas implicated in emotion regulation and cognition. In addition, these findings may implicate abnormal integrity of anterior cingulate cortex in the psychophysiological expression of GAD and suggest that interventional targeting of this region may normalize autonomic function in GAD.